Phytochemical and mineral composition of fruits and seeds of wild-growing Bactris guineensis (L.) H.E. Moore palms from Costa Rica - Erşan, Sevcan (2020)
In the present study, nutritionally relevant constituents of wild-growing B. guineensis palm fruit from Costa Rica were assessed. In the edible exo- and mesocarp, 24 soluble free and six insoluble bound phenolic compounds were found. Anthocyanins, catechin mono- and oligomers, quercetin O-glycosides, in addition to apigenin- and luteolin C-glycosides were identified in the soluble free fraction, totalling to 17 and 398 mg/100 g of fresh weight (FW) in the meso- and exocarp, respectively. The insoluble-bound phenolic compounds exclusively comprised phenolics acids (9.4 and 39 mg/100 g of FW, respectively). Among 15 different carotenoids, (all-E)-β-carotene and (all-E)-lutein prevailed. Total carotenoid levels in meso- and exocarp amounted to 363 and 1728 μg/100 g of FW, respectively. Among tocochromanols, merely α-tocopherol was found in quantifiable concentrations (230 and 2401 μg/100 g of FW, respectively). In the kernel, total lipids represented 34.1% of the dry matter, mainly consisting of saturated fatty acids (90.0%). Hereby, lauric (56.3%) and myristic acid (23.0%) were the most abundant ones. Nutritionally relevant elements of the exocarp, mesocarp, and kernel were assessed by ICP-MS. In particular, the kernel was rich in magnesium and iron (68 and 2.65 mg/100 g of FW, respectively) and hence, a good nutritional source for these elements. Concluding, the present study is the first detailed report on the composition of the edible fractions of B. guineensis fruit, highlighting the nutritional, but also the hitherto unexploited industrial potential of this underutilised crop.